Analisis Perilaku Konsumsi Telur Ayam Ras oleh Rumah Tangga Peserta Program Keluarga Harapan di Kota Pekanbaru - Ramadhani, Anisa; Bakce, Djaimi; Novian, Novian (Jurnal Ilmiah Fillia Cendekia, 2026)
This study is motivated by the increasing price of broiler chicken eggs and the high dependency of low-income households in Pekanbaru City, particularly beneficiaries of the Program Keluarga Harapan. The objective of this study is to identify the dominant factors influencing broiler chicken egg consumption and to analyze household responses to these dominant factors among PKH beneficiary households in Pekanbaru City. A quantitative approach was employed using a survey method involving 315 PKH beneficiary households in Pekanbaru City as respondents. Data were analyzed using multiple linear regression and demand elasticity analysis.The results indicate that six variables significantly affect broiler chicken egg consumption among PKH beneficiary households in Pekanbaru City, namely the price of broiler chicken eggs, household income, household size, chili price, other onion prices, and fresh fish prices, as evidenced by significance values (P < 0.2). Broiler chicken egg consumption among PKH beneficiary households in Pekanbaru City is elastic with respect to egg prices, indicating that an increase in prices leads to a proportionally larger decrease in consumption. Meanwhile, the elasticities of income, household size, fresh fish prices, other onion prices, and chili prices are classified as inelastic.These findings indicate that broiler chicken eggs constitute a staple food that continues to be consumed despite changes in economic conditions; however, consumption remains sensitive to price increases. Overall, this study emphasizes the importance of price stabilization and improved access to nutritious food for low-income households as efforts to strengthen food security.”